Quality Evaluation of Pulsatilla chinensis Total Saponin Extracts via Quantitative Analysis of Multicomponents by Single Marker Method Combined with Systematic Quantified Fingerprint Method - Long Chen; Suzhen Liu; Shuhan Feng; Liangliang Zhou; Zhenhua Chen (Journal of Analytical Methods in Chemistry)
Chinese medicine extracts are complex in composition. The combination of the quantitative analysis of multicomponents by single marker (QAMS) and the systematic quantified fingerprint method (SQFM) can be used for better quantitative analysis. The contents of Pulsatilla saponin D, Pulsatilla saponin A, Pulsatilla saponin F, and oleanolic acid 3-o-β-d-pyranoglucosyl-(1⟶4)-β-d-pyranoglucosyl-(1⟶3)-α-l-pyridine rhamnosyl-(1⟶2)-α-l-pyranosine arabinoside (B9) were determined by HPLC and QAMS. The methodological verification was carried out. The relative correction factor (RCF) was calculated, and the reproducibility of the RCF was investigated. The experimental results of the external standard method (ESM) and the QAMS were compared. Meanwhile, the fingerprint of the extract of Pulsatilla chinensis total saponins was established and the quality of the extract was evaluated by SQFM and hierarchical cluster analysis (HCA). The results showed that there was no significant difference between the QAMS and ESM. QAMS could be used for the rapid determination of various saponins in the extract of Pulsatilla chinensis. SQFM and HCA could objectively and comprehensively reflect the overall quality difference of total saponin extract of Pulsatilla chinensis. Therefore, QAMS and SQFM could provide a more convenient and effective selection for the quality evaluation of total saponin extract from this plant.